Urological problems in gynecological surgery - Esteves F., Luis (2015)
The intimate relationship between urinary and genital structures of women, both anatomically and pathologically order creates problems of surgical gynecologist, of great importance and significance to the patient; The specialist should know warning and try and avoid if possible. Moreover, modern gynecological cancer surgery, sometimes called a radical and other ultra-radical, raises, as far as urinary diversion is concerned, situations or conditions that definitely alter the anatomy and physiology of the patient; thereby creating a state of permanent disability, on the one hand, the patient should know and accept, and on the other, the surgeon should lessen with choosing the best type of surgical procedure and with the use of prosthetic devices to this end they have been created. Thus, the plan of this work is not primarily concern the operative accidents and complications involving the urinary system during gynecological surgery, which, moreover, are well known by those who practice and are very well exposed in all modern treaties gynecology and in numerous publications and well documented.